USAGE OF MODERN TOOLS AND SOFTWARE IN TEACHING METHODOLOGY -A CASE STUDY - SUBBULAKSHMI , M.; PONSHANMUGA KUMAR, A. (International Journal of Psychosocial Rehabilitation, 2020)
he article focuses on the utilization of modern tools in Technical education. A detailed survey is taken among students (UG, PG and Research Scholars) who pursue technical education in various Engineering colleges of Tamilnadu. Many parameters are widely used by the students for learning, are taken into consideration for the process of making survey. The paper also discusses on the output of the survey that to find which tool is mostly liked by the students and what is the reason behind it. This paper also analyzes the software mostly used by the students. The above mentioned points are taken into consideration for the discussion on the usage of the modern tools and software in a technical classroom to enhance their learning process.